An Investigation Of Undergraduates' Language Learning Strategies - Hakan, Karatas; Aydin, Balyer; Bulent, Alci (ELSEVIER SCIENCE BV, 2015)
Learning strategies are steps taken by students to enhance their own learning. Strategies are especially important for language learning because they are tools for active, self-directed involvement, which is essential for developing communicative competence (Oxford, 1990). Language learning strategies also enable students to gain a large measure of responsibility for their own progress. This study aims to determine undergraduates' language learning strategies and relationship with gender. The participants of the study were composed of 120 undergraduates from different departments and attending in English preparation class. To determine undergraduates' language learning strategies, the data were collected using Strategy Inventory for Language Learning (SILL), originally developed by Oxford (1990) and Turkish bilingual equivalence, validity and reliability of which carried out by Cesur and Fer (2007), was used. The analysis of independent samples of t-test was conducted to clarify the language learning strategies of undergraduates in terms of gender. The results reveal that significant differences were found in undergraduates' language learning strategies relating to gender. These findings and implications for educational researchers and the significance of such individual differences in language learning strategies were discussed (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Language learning strategies; undergraduates; language proficiency; gender; STUDENTS; Education & Educational Research; Social Sciences - Other Topics